Prevalent races of wheat rust pathogens in Lebanon, Morocco and Tunisia in 2023 - Nazari, Kumarse; El Amil, Rola; Al-Jaboobi, Muamar; Maafa, Ilyass; Kemal, Seid Ahmed; Ramdani, Abdelhamid; Ibriz, Hafid; SBAI, Ibtihel; Ramdhane, Nasraoui; Abdsattar, Bouslimi (International Center for Agricultural Research in the Dry Areas, 2023)
In 2023, the rust surveys conducted in Lebanon yielded 110 samples, comprising 42 stem rust, 28 yellow rust, and nine leaf rust samples. Similarly, 16 stem rust, eight yellow rust, and seven leaf rust samples were collected from Morocco during the rust surveys, while 28 yellow rust samples were collected from Tunisia. Unfortunately, the Tunisian samples couldn't reach the RCRRC. Because of poor sampling conditions, the recovery of yellow rust samples was not successful. Stem race analysis involved 90 isolates, including 55 isolates from the 2022 rust surveillance. Sixteen stem rust races were identified, with the TKKTF, TKTTF, TTTTF, and PKTTF races being predominant in both countries. No evidence of the Ug99 race with Sr31 virulence has been found. Leaf rust samples were subjected to purification and spore multiplication, and ongoing race analysis aims to determine the leaf rust race.